Prophylactic intravenous immunoglobulin use in allogeneic stem cell transplantation; does intravenous immunoglobulin affect survival, sepsis, and engraftment time? - Ahmet Kaya; İlhami Berber; İrfan Kuku; Emin Kaya; Mehmet Ali Erkurt; Soykan Biçim; Süleyman Arslan; Fatma Hilal Yağin (Iraqi Journal of Hematology)
BACKGROUND: Stem cell transplant recipients have an increase in various infections depending on the immunosuppression. The purpose is to explore the effect of the use of proflactıc intravenous immunoglobulin (IVIG) on transplant recıpıents. OBJECTIVE: It was aimed to examine the effect of IVIG on allogeneic stem cell transplantation. MATERIALS AND METHODS: In this study, sepsis status, infection focus causing sepsis, neutrophil and platelet engraftment time of patients the length of stay in the hospital at the time of the stem cell transplant, if the patient died, how many days after the transplant the event developed, and the data of the bone marrow transplant unit were reviewed retrospectively. One hundred and eleven patients who were given IVIG (400 mg/kg/week IVIG intravenous was given to the patients as a weekly prophylactic up to 100 days starting on the 7th day after transplantation) and 190 patients who did not receive IVIG were included in the study. RESULTS: There was no statistically significant difference between the IVIG groups in terms of gender, diagnosis, donor characteristics, and event (P > 0.05). Sepsis was observed significantly less in patients who were given IVIG compared to patients who were not given IVIG (P < 0.001). While it was observed that IVIG did not have a significant effect on platelet engraftment and discharge times (P > 0.05), neutrophil engraftment time was significantly higher in patients given IVIG compared to patients not given IVIG (P < 0.009). It was observed that the use of IVIG in patients with sepsis did not have a positive effect on survival. (with sepsis hazard ratio [HR]: 3.890 P = 0.001, IVIG given HR: 3.244 P = 0.035). CONCLUSION: It was observed that the use of IVIG in allogeneic stem cell transplantation was associated with a decrease in sepsis, but the use of IVIG did not have a positive effect on survival and could prolong neutrophil engraftment.